Identidade e negritude: cor negra e cabelo crespo sob o olhar de alunos de uma escola pública no km 14, Irituia (PA) - AMORIM, Francisca Andréia Gonçalves de (2019)
This work aims to analyze the conceptions of adolescent students about black aesthetics, from their looks on curly hair and black color, in order to highlight the implications of these conceptions in the process of affirmation and valorization of black identity. To do so, it addresses historical, social and educational considerations that permeate oppression and empowerment contexts of the country's ethnic-racial relations. In the methodological procedures of the research, the case study approach was used, with a quantitative-qualitative approach, in which the subjects surveyed were 78 students from the final years of elementary and high school at Nicolau Neres da Silva School, located at Km 14, municipality of Irituia, state of Pará. As a theoretical contribution of the discussions, authors such as Gomes (2002, 2003), Munanga (1999, 2009), Domingues (2008), Figueiredo (2002) and Oliveira (2015) were used. Based on the results of the analysis, it was verified that the students' conceptions about the black esthetics are mostly positive, pointing out significant advances in the problems of the racial question of the country, however, these conceptions are still insufficient for the effective affirmation and enhancement of black identity. The data also pointed to the occurrence of black color discrimination and African ancestry hair at school, and that these causes problems in school life and the acceptance of blackness.